(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The term live arts, used as analogous to performing arts, began to be used in the 1960s to refer to an expanded conceptualization of visual and performative arts, which impact on contemporary theatricalities involves a detachment from the forms of bourgeois realist drama: that is, the distance from what is still hegemonically referred to as theater. In terms of this distance, the vindication of the living (or liveness) and its links with certain modes of presence has been recurrent. This paper focus on the ways in which the Spanish stage of the 21st century updates what is conceived as liveness, based on the questioning of mimetic-realistic acting. How is the living thought, theatrically, on the margins or against acting?